MexXY Multidrug Efflux System Is More Frequently Overexpressed in Ciprofloxacin Resistant French Clinical Isolates Compared to Hospital Environment Ones - Serra, Cristiano; Bouharkat, Bakhta; Tir Touil-Meddah, Aicha; Guénin, Stéphanie; Mullié, Catherine (Frontiers in Microbiology, 2019)
Modulation of the membrane permeability through a decrease in porin-mediated antibiotic entry and/or an increase in antibiotic efflux is one of the resistance mechanisms to antibiotics evolved by Gram-negative bacteria. To assess whether the outer membrane porin OprD and Resistance-Nodulation-Division (RND) efflux pumps were similarly expressed in 33 ciprofloxacin-resistant clinical strains of Pseudomonas aeruginosa and in 30 non-clinical strains originating from the hospital environment (mainly waterborne Pseudomonas aeruginosa), the expression of oprD, mexB, mexF and mexY genes was investigated. Overall, the expression of oprD was not detected by RT-qPCR in 14 (22%) strains and underexpressed in 35 (56%) more. No significant difference in oprD expression was detected between clinical and non-clinical strains. As for efflux pumps, 23 (70%) of the clinical strains overexpressed at least one of the tested RND genes. Overexpression of mexB, mexF and mexY was detected in 27%, 12% and 45% of the clinical strains, respectively. In the 30 non-clinical strains, no overexpression could be found for mexB, mexF or mexY. On the contrary, a global underexpression of the tested efflux pump genes was recorded. In both clinical and environmental strains, a positive correlation was found between the expressions of oprD and mexB. Similarly, the expressions of oprD and mexF were positively correlated. This result contrasts with the inverse correlation between both MexAB-OprM/MexEF-OprN and OprD previously described in carbapenem-resistant P. aeruginosa strains. The only positive correlation between phenotypic ciprofloxacin minimum inhibitory concentrations (MICs) and the expression of efflux pump gene was witnessed with mexY (analysis on pooled results for clinical and environmental strains). However, in clinical strains, no statistically significant link could be found between the degree of reduction in ciprofloxacin MICs witnessed with Phenylalanine-Arginine β-naphthylamide (PAβN) and the expression of any of the 3 RND genes tested.